Postoperative delirium in patients with cancer: a narrative review of major risk factors - Oliveira, Alessandra Bittencourt de; Handa, Adriana Mayumi; Sakai, Eduardo; Morais, Arthur Caus de; Quezada, Michael Madeira de la Cruz; Mitsunaga Junior, Jorge Kiyoshi; Portugal, Assaiah Moreira Marrazzo da Costa; Joaquim, Eduardo Henrique Giroud; Nakamura, Giane (São Paulo Medical Journal, 2026)
BACKGROUND: Postoperative delirium (POD) is a severe complication and the most frequent adverse event in older patients, particularly those with cancer. With the increase in the older surgical population and cancer diagnoses, the incidence of POD is expected to increase. OBJECTIVES: To identify and evaluate major risk factors for POD in patients with cancer. DESIGN AND SETTING: Narrative review conducted at the A.C.Camargo Cancer Center in São Paulo, Brazil. METHODS: PubMed, LILACS, and Embase database searches were conducted using relevant keywords from June 2023, to September 2024. We identified 279 studies; after screening and applying the eligibility criteria, 49 studies were included in the analysis. RESULTS AND DISCUSSION: POD risk factors in patients with cancer are associated with inflammation and the cumulative burden of intensive therapeutic modalities. These factors can be categorized into three domains: directly related to cancer, indirectly related to cancer, and preexisting predisposing factors. Among these factors, age is important. Additional relevant contributors include frailty, cognitive impairment, sarcopenia, pain, anxiety, and depression. A complex interaction exists between these factors that renders POD management in patients with cancer challenging; however, the impact of each factor remains unclear. CONCLUSION: Multiple overlapping risk factors often contribute to POD development in patients with cancer. Age is a significant risk factor, as reported in the literature. Other relevant factors have been described; however, the relative contribution of each factor to the etiology of POD remains unclear. Further research is required to address this knowledge gap.